THE DECISION-MAKING PROCESS IN CHARLES EDWARD LINDBLOM AND THE GENERAL WILL IN JEAN-JACQUES ROUSSEAU: REFLECTIONS ON POLITICAL PARTICIPATION AND THE NEED FOR EDUCATION FOR THAT PARTICIPATION - Sbrana, Roberta Aline [UNESP]; Assumpcao, Flaviana Christine V. P. M. [UNESP]; Goulart, Joana Correa; Lemes, Sebastido de Souza [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
In The Policy-Making Process, Charles Edward Lindblom reflects upon such process, highlighting the relevance of the political participation of the general citizens. Nevertheless, the author warns the reader about the necessity of the existence of a kind of education that commits to the formation of men and women for social participation since, only because of this kind of education, such participation will be carried out. Likewise, in The Social Contract, Jean-Jacques Rousseau presents considerations about the importance of a people's participation in the elaboration process of such contract, which shall happen through general will. Nonetheless, such participation entails a kind of education towards the formation of men as individuals and citizens in order for them to participate actively in society, as he exposes in his pedagogical treatise - Emile or On Education. This paper aims to foreground that, in both reflections, the authors discuss about the relevance of the political participation of the citizens, which, according to their point of view, shall fully happen only through the existence of a kind of education that values formation for participation.
Keywords: Decision-making process; General will; Participation; Education